2013
DOI: 10.1371/journal.pone.0063944
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Osteopontin with IL-18 in Obese Individuals: Implications for Insulin Resistance

Abstract: Background/ObjectiveOsteopontin (OPN) and IL-18 are known inflammatory mediators and both participate in a wide range of biological processes linked to immunological disorders. Since an interaction between OPN and IL-18 has not been studied in obesity, we investigated whether: (i) their levels were simultaneously elevated in obese individuals; (ii) OPN was associated with IL-18 in obese individuals and (iii) their levels associated with fasting blood glucose (FBG) and BMI.Subjects and MethodsPBMCs and plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 44 publications
4
51
1
Order By: Relevance
“…Increased OPN levels were found in obese participants (12,13) and predicted coronary calcification, nephropathy and coronary artery disease in patients with type 2 diabetes, independent of traditional risk factors (14,15).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Increased OPN levels were found in obese participants (12,13) and predicted coronary calcification, nephropathy and coronary artery disease in patients with type 2 diabetes, independent of traditional risk factors (14,15).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, serum OPN levels were demonstrated to strongly predict incipient diabetic nephropathy (DN), cardiovascular events and all-cause mortality in patients with T1DM (26) and were associated with renal failure and left ventricular hypertrophy in patients affected by systemic hypertension (27,28). Furthermore, in a recent study, obese individuals exhibited significantly increased blood OPN levels and higher adipose tissue/peripheral blood mononuclear cells OPN expression compared with lean individuals; OPN also correlated with fasting blood glucose (FBG) and BMI (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, these two studies have demonstrated that fat loss produced a statistically significant reduction in circulating OPN concentration [43,44] . In addition, high levels of serum OPN were found in obese individuals [42,43,45] . These findings suggest that adipocytes may be one origin of circulating OPN levels.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, more recently, simultaneous up-regulation of IL-18 and OPN in peripheral blood mononuclear cells (PBMCs) has been reported in obese individuals as compared to lean subjects. Intriguingly, treatment with a neutralizing IL-18 antibody diminished OPN secretion from PBMCs, indicating that IL-18 regulates OPN expression [137]. These findings point toward a specific pathophysiological role of OPN also in human inflammatory processes linked to obesity-induced adipose inflammation, insulin resistance, type 2 diabetes and its complications.…”
Section: Obesity and Bone Metabolism: Energy Homeostasis Hormone Bomentioning
confidence: 77%